Life cycle assessment of emerging mass timber product: Cross-laminated bamboo - Yinqiao Wang; Kai Lan (Cleaner Environmental Systems)
Cross-laminated bamboo (CLB) is a new type of mass timber product that can be a substitute for traditional non-renewable construction materials. This study conducted a cradle-to-grave life cycle assessment (LCA) to quantify the environmental impacts of CLB panels over 100 years. The LCA was integrated with process model simulation to explore the effects of varied fuel options (combusting bamboo residues or converting bamboo residues into biochar and combusting natural gas) and end-of-life cases on the results, and coupled with Monte Carlo simulation to investigate the uncertainties and variabilities associated with the CLB life cycle stages. Our results show that, on the 1 m3 CLB basis, the average life-cycle global warming potential (GWP) ranged from −318 to −947 kg CO2eq. Combusting the bamboo residues from production processes resulted in lower life-cycle GWP than utilizing bamboo residues to produce biochar and burning natural gas for energy supply. Increasing the recycling rate of CLB panels can further reduce the life-cycle GWP. The landfill decay of bamboo wastes is a significant carbon emission source, highlighting the importance of considering end-of-life cases for CLB panels. Trade-offs emerge among varied environmental impact categories when the scenarios are compared.